How to address cerebrospinal fluid leakage following ossification of the posterior longitudinal ligament surgery. (November 2017) - Moon, Jung Hyeon; Lee, Sungjoon; Chung, Chun Kee; Kim, Chi Heon; Heo, Won
Highlights: The risk of CSF leakage in ossified posterior longitudinal ligament (OPLL) surgery is especially high because adhesion of the dura to the ossified PLL is common, especially in the anterior resection of OPLL. Based on several years of our experiences, we present our concept for addressing cerebrospinal fluid (CSF) leakage following dural tear during anterior OPLL surgery. Abstract: Background: Primary dural repair in ossification of posterior longitudinal ligament (OPLL) surgery via anterior is challenging because of limited space. Based on several years of our experiences, we present our concept for addressing cerebrospinal fluid (CSF) leakage following dural tear during anterior OPLL surgery. Methods: We reviewed the medical records of 65 patients who underwent anterior OPLL surgery from 2003 to 2014. We included 7 patients whose operation records described dural tear followed by CSF leakage. Primary dural repair could not be performed in 6 patients because of ragged tear and limited space. We managed them with our own strategy: simple cover with an artificial dura, collagen sponge and/or fibrin glue on defect site; anatomical layer-by-layer repair without either subfascial or CSF drain, and early ambulation. Results: Of 7 patients, wound problems developed in 2 patients. Wound aspiration and antibiotic treatment was done without wound compression in one patient, and simple irrigation followed by anatomical layer-by-layer re-closure was done in the other patient without either bed rest or lumbar drainage. Pseudomeningoceles were detected in 4 patients, including 2 patients who had wound problems. However, all pseudomeningoceles were absorbed spontaneously or stabilized on follow-up images without interventions such as bed rest, lumbar drain or wound compression. Conclusions: Without interference of pressure equilibrium between intradural and extradural space, the defect site would heal and close. After that, the isolated pseudomeningocele would be spontaneously absorbed after certain period of time.